Micropropagation of Two Caladium Species - Sakpere, A. M. A.; Adebona, A. C. (2014)
Great differences occur in cell division and regenerative capacity between plants even within a single species. Therefore difference in callus induction and plant regeneration abilities of two Caladium species - Caladium bicolor and Caladium humboldtii was studied by culturing them on different combinations of growth regulators. Caladium humboldtii was found to be the more responsive genotype for callus induction while Caladium bicolor was the more responsive genotype for plant regeneration. Roots and shoots were more readily generated on corm explants in combinations of Kinetin and Naphtalene Acetic Acid (NAA) than in media containing different concentrations of 2,4-dichlorophenoxy acetic acid (2,4-D) and 1 mg/L Kinetin. Callus was generated on tubers of both species on media supplemented with 0.8 mg/L 2,4-D and 1 mg/L Kinetin.